2010
DOI: 10.1074/jbc.m109.073791
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic 5-HT2B Receptor Controls Tissue-nonspecific Alkaline Phosphatase Activity in Osteoblasts via Eicosanoids and Phosphatidylinositol-specific Phospholipase C

Abstract: In previous studies, we observed that mice knocked out for the serotonin-2B receptor (5-HT 2B R) show defects in bone homeostasis. The present work focuses on the downstream targets relaying the anabolic function of this receptor in osteoblasts. A functional link between the 5-HT 2B R and the activity of the tissue-nonspecific alkaline phosphatase (TNAP) is established using the C1 osteoprogenitor cell line. During C1 osteogenic differentiation, both 5-HT 2B R and TNAP mRNA translations are delayed with respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 36 publications
8
20
0
Order By: Relevance
“…Another report showed that PGE2 stimulates the osteogenic differentiation of cultured tendon stem cells via BMP-2 induction 18) . Taken together, these previous reports 2,17,18) appear to support the hypothesis that eicosanoids produced via the PLA2 pathway contribute to the process of ectopic osteogenesis in cardiac valves.…”
Section: Cultures Of Valve Interstitial Cells (Vics)supporting
confidence: 65%
See 1 more Smart Citation
“…Another report showed that PGE2 stimulates the osteogenic differentiation of cultured tendon stem cells via BMP-2 induction 18) . Taken together, these previous reports 2,17,18) appear to support the hypothesis that eicosanoids produced via the PLA2 pathway contribute to the process of ectopic osteogenesis in cardiac valves.…”
Section: Cultures Of Valve Interstitial Cells (Vics)supporting
confidence: 65%
“…In line with the present findings, a previous report showed that the 5-LOX expression is increased in calcified human aortic valves and that the incubation of myofibroblast cultures with LTC4, a 5-LOX metabolite, induces calcium nodule formation 2) . In cultures of tendon stem cells, serotonergic receptor signals have been shown to stimulate tissuenonspecific ALP through the actions of eicosanoids produced via the PLA2 pathway 17) . Another report showed that PGE2 stimulates the osteogenic differentiation of cultured tendon stem cells via BMP-2 induction 18) .…”
Section: Cultures Of Valve Interstitial Cells (Vics)mentioning
confidence: 99%
“…5-HT 2B receptor expression during osteoblast differentiation in vitro was shown to be increased in primary cultured mouse osteoblasts (Hirai et al, 2009), and the ablation of the 5-HT 2B receptor in female mice led to osteopenia due to impaired bone formation (Collet et al, 2008). In addition, 5-HT 2B receptor signaling in osteoblasts was found to regulate cellular proliferation, differentiation, and functions (Baudry et al, 2010;Locker et al, 2006;Li et al, 2013). Previous studies e confirmed the pattern of expression for the 5-HT receptor in osteoblastic cells (Hirai et al, 2009).…”
Section: Discussionmentioning
confidence: 53%
“…This mode of osteoblast regulation by Htr1b is relevant to studies reporting an opposite, bone-protective effect of the Htr2b receptor in osteoblast function (46,47). To exclude the possibility that the anabolic effect of Htr1b deletion could be due to upregulation of Htr2b, we measure its expression in our mouse models.…”
Section: Discussionmentioning
confidence: 99%